Pengelolaan Sarana Pembelajaran pada SD Negeri Belah I Donorojo Pacitan - Luqman Hadi (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2017)
The objectives of the research are to describe the characteristics of: 1) the learning facilities planning; 2) the utilities of learning facilities; and 3) the maintenance of learning facilities at SDN Belah I Donorojo Pacitan to facilitate the teaching and learning process. The type of the research is qualitative research. The design of the research employed was ethnographic study. The data collecting method was done using in-depth interviewing, observation, and document techniques. The data analysis was done using single case analysis design. The analysis design selection for qualitative research conveys three main components, namely data reduction, data display, and verification. The data validity is done using triangulation, key informant review and member-check techniques. The research concludes that: 1) the characteristics of learning facilities planning at SDN Belah I Donorojo Pacitan was initiated by arranging proposal proposed to get the aids from Ministry of Education, Provincial Budgetting, and Municipal’s Budgetting. The learning facilities development was done within the establishment of 15 programs of school’s learning facilities. The school learning facilities were financed through school’s budgetting. Th e finance were allocated from parental aids and governmental aids in the form of block grant schemes; 2) The learning facilities utilities at SDN Belah I Donorojo Pacitan were done optimally. The learning facilities were utilitized as students’ competence exploration tools, namely used as students’ creativities and innovation tools. The learning facilities controlling strategies were done by teacher that specifically assigned to manage the school’s learning facilities; and 3) the learning facilities maintenance of multimedia laboratory was done cooperatively with the computer suplier by special contract system. It is done with the effectivity consideration so that the teacher may focus their attention in teaching and learning process and the facilities wer e ready to be used at any time.